MEMBANGUN KEPEMIMPINAN VISIONER DI ERA DISRUPSI: TELAAH LITERATUR TEORITIS - Gafur, Abdul (Kybernology Jurnal Ilmu Pemerintahan dan Administrasi Publik, 2025)
The era of disruption, characterized by rapid change, high uncertainty, and organizational complexity, demands the presence of leaders with a strong futureoriented vision. This article aims to present a theoretical literature review on visionary leadership by highlighting its key characteristics, strategic relevance, and implementation challenges within modern organizational contexts. Using adescriptive-qualitative approach based on library research, this study analyzes various theories and perspectives on the role of visionary leaders in driving transformation and innovation. The findings indicate that visionary leadership is crucial in shaping an organization's strategic direction, inspiring collaboration, and fostering resilience amid disruption. However, its implementation requires supportive organizational culture, leadership capacity, and the courage to overcome resistance. Therefore, investing in the development of visionary leadership is an urgent necessity for building adaptive and sustainable future organizations